La estructura del reportaje en radio - Herrera Damas, Susana (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
The feature is a model of representation of the reality that from the monologue tries to narrate and describe facts and actions of interest for the listener, providing a wide context of interpretation in the contents and a use of sources diverse and creative. As most of the audio-visual texts, it is constructed in three parts: opening, development and closing. The aim of this article is to describe the function and the requirements that correspond to each of these parts and to expose also the different types of openings, developments and closings that construct features in radio.